The development of Southeast Asia’s digital economy: current status, development motivation and challenges - Yu, Miao (Economic and Regional Studies / Studia Ekonomiczne i Regionalne, 2024)
NOABSTRACTThis paper aims to contribute to the understanding of the digital economy in Southeast Asia (SEA). It evaluates SEA’s digital economy industry from various perspectives, analysing the reasons for its rapid development as a non-core innovation area of the digital economy.A comprehensive literature review and descriptive methodology were used to produce this paper. The methods used included defining the evaluation criteria of the digital economy and summarising and sorting out the development of SEA’s digital economy.With respect to theory, this paper analyses the current status of SEA’s digital economy, which helps deepen our understanding of the new trends in SEA’s economic development. As regards practicalities, it provides suggestions for how SEA countries can further improve the development model of the digital economy.The paper assesses SEA’s digital economy and identifies the driving factors that enable the region to rapidly develop digital economy industries. The first set of factors are national-level policies, a unified market, population structure, and mobile penetration rate. The second set of factors are regional, as SEA can benefit from digital economic spillover from countries such as China and the United States. The third set of factors is global. The transfer of the global industrial chain has also facilitated the development of the digital economy in the region. This paper hypothesises that national-level factors are decisive, enabling a non-core innovation area such as SEA to develop rapidly, while regional-level and global-level factors are auxiliary.